Rock cá, rock lá: a produção roqueira no Brasil e em Portugal na imprensa : 1970/1985 - Encarnação, Paulo Gustavo [UNESP] (2015)
This doctoral thesis historical-comparatively deals with and reflects about the significance of producing rock in Brazil and Portugal between 1970 and 1985, and the role played by the genre and its products into the cultural-political debate and confrontation, intermingled then by dichotomies such as national/foreign and alienated/politicized. The understanding and the possible plausible explanations of this historical framework allow us to know, understand and interpret some rock songs containing criticism of Brazilian as well as Portuguese social and political life, both marked at the time by dictatorships and democratization processes. Thus, this work seeks to know and understand how rock, in general, has historically been seen and defined by both rockers and different agents of the cultural field and the media. Also, it covers rockers and cultural and media agents' views and assessments on rock within a logic of marginality and in the light of stereotypes concerning the youth rebellion and violence - whether arising from the rocker universe or foisted to it by agents and social institutions and different policies. And it focus, on the one hand, how in Brazil and in Portugal rock and its agents have been positioned in the cultural-political debate that, among other issues, has attempted to define rock as domestic or foreign, and on the other, the ways in which Brazilian and Lusitanian rockers and songs integrated confrontations that sought to identify the rock as alienated or politicized; always bearing in mind the actions of various cultural agents and the media relating to such segments. Such path makes it possible to argue that the rock produced in Portuguese language in Brazil and in Portugal since the 1950s went through a process of nationalization that would culminate, from the 1970s and, with special emphasis in the first half of the 1980s, the so-called national rock, which...